Epistemology as Politics and the Double-bind of Border Thinking: Lévi-Strauss, Deleuze and Guattari, Mignolo - Timothy Nicholas Laurie (PORTAL: Journal of Multidisciplinary International Studies, 2012)
This paper examines Gilles Deleuze and Felix Guattari’s theories of writing and the State in Anti-Oedipus and A Thousand Plateaus, teasing out issues of gender, primitivism and academic expertise in the authors’ claims about power and politics. While noting the benefits of politically analysing social customs and traditions, Laurie highlights the complicities between Deleuze and Guattari's theories and the assumptions embedded in their anthropological sources. He further argues that the cultural and historical speculations in Anti-Oedipus cannot be divorced from the authors' privilege of philosophy as a uniquely European creative space. Seeking an alternative perspective on cultural translation, the paper turns to Walter Mignolo’s study of the 'book' in Spanish-Amerindian colonial encounters. Foregrounding the critical value of philology for ‘de-colonising’ theory, Mignolo argues that Eurocentric cultural comparisons serve to legitimate particular ways of knowing within contested fields of representation. However, in both Deleuze and Guattari and Mignolo, the paper questions the gender dynamics of writing practices implicitly articulated in meta-narratives about the State and/or colonialism. Laurie suggests that these authors frequently remain oblivious to the role of women in the historical contexts examined, and that understanding political dynamics within cultural groups requires questioning the privilege of writing itself, both in and outside the academy. While sympathetic to the role of political philosophy in negotiating complex historical issues, this paper also advocates a rethinking of the subordinate place attributed to anthropological and historical research practices in the theoretical exegeses of Deleuze, Guattari and Mignolo.